2021
DOI: 10.1111/jocn.16035
|View full text |Cite
|
Sign up to set email alerts
|

Frailty measurements in hospitalised orthopaedic populations age 65 and older: A scoping review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
(101 reference statements)
0
22
0
Order By: Relevance
“…Wahl et al [10] studied the association of MFI with 30 days' surgical readmissions in orthopedics, general surgery, and vascular surgeries. Roopsawang et al [11] studied various frailty measurements in orthopedic populations aged more than 65 years and concluded that various frailty indices have been used in the orthopedic setting; however, evidence is still lacking for the gold standard frailty index. We feel that since frailty is subjective and difficult to measure, it is difficult to get an ideal frailty index.…”
Section: Introductionmentioning
confidence: 99%
“…Wahl et al [10] studied the association of MFI with 30 days' surgical readmissions in orthopedics, general surgery, and vascular surgeries. Roopsawang et al [11] studied various frailty measurements in orthopedic populations aged more than 65 years and concluded that various frailty indices have been used in the orthopedic setting; however, evidence is still lacking for the gold standard frailty index. We feel that since frailty is subjective and difficult to measure, it is difficult to get an ideal frailty index.…”
Section: Introductionmentioning
confidence: 99%
“…While it is widely accepted that increased age serves as an indicator to predict postoperative complications, however, because the heterogeneity of different population, some younger people can be frail, and some older people can be robust. 16 In recent years, the 5-item Fried frailty phenotype was one of the most commonly used indexes evaluating 22 Nevertheless, on the one hand, in previous literatures, comparing frailty and age, the superiority of predicting postoperative complications was the focus. In a retrospective analysis of 199 patients, Leung et al 23 demonstrated that age was a significant moderator of the relationship between pre-frail and body measures.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In recent years, the 5-item Fried frailty phenotype was one of the most commonly used indexes evaluating postoperative outcomes. 22 Nevertheless, on the one hand, in previous literatures, comparing frailty and age, the superiority of predicting postoperative complications was the focus. In a retrospective analysis of 199 patients, Leung et al 23 demonstrated that age was a significant moderator of the relationship between pre-frail and body measures.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely accepted that increased age serving as an indactor to predict postoperative complications, however, because the heterogeneity of different population, some younger people can be frail, and some older people can be robust [16]. In recent years, frailty, as distinguished by 5-item Fried frailty phenotype was one of the most commonly uesd to evaluate postoperative outcomes [22]. Nevertheless, on one hand, in previous literatures, comparing frailty and age the superiority to predict postoperative complications was the focus.…”
Section: Discussionmentioning
confidence: 99%